Gamma-ray spectrum from thermal neutron capture on gadolinium-157. (22nd February 2019) - Hagiwara, Kaito; Yano, Takatomi; Tanaka, Tomoyuki; Reen, Mandeep Singh; Das, Pretam Kumar; Lorenz, Sebastian; Ou, Iwa; Sudo, Takashi; Yamada, Yoshiyuki; Mori, Takaaki; Kayano, Tsubasa; Dhir, Rohit; et al.
Abstract: We have measured theγ -ray energy spectrum from the thermal neutron capture, ^157 Gd(n, γ), on an enriched^157 Gd target (Gd_2 O_3 ) in the energy range from 0.11 MeV up to about 8 MeV. The target was placed inside the germanium spectrometer of the ANNRI detector at J-PARC and exposed to a neutron beam from the Japan Spallation Neutron Source (JSNS). Radioactive sources (^60 Co, ^137 Cs, and^152 Eu) and the^35 Cl(n, γ ) reaction were used to determine the spectrometer's detection efficiency forγ rays at energies from 0.3 to 8.5 MeV. Using a Geant4-based Monte Carlo simulation of the detector and based on our data, we have developed a model to describe theγ -ray spectrum from the thermal^157 Gd(n, γ ) reaction. While we include the strength information of 15 prominent peaks above 5 MeV and associated peaks below 1.6 MeV from our data directly into the model, we rely on the theoretical inputs of nuclear level density and the photon strength function of^158 Gd to describe the continuumγ -ray spectrum from the^157 Gd(n, γ ) reaction. Our model combines these two components. The results of the comparison between the observedγ -ray spectra from the reaction and the model are reported in detail.